The moderating role of economic freedom, culture and corruption on socio cognitive traits and entrepreneurship using institutional economics theory - Mendoza, Enrico C. (Animo Repository, 2020)
In 2016, global economy grew by a measly 2.2 percent (United Nations, 2017) due to declines in global trade and global investment. Given the sluggish global economy, putting it back on its feet thru the help of entrepreneurs can be considered critical. Considering that prior studies have strongly argued how entrepreneurship can be an engine that can help drive up the vehicle of economic growth and development (Angulo-Guerrero et al., 2017; Estrin et al., 2013) while also not forgetting that individual decision to enter entrepreneurship is a function of the type and quality of institutions (North, 1991), it is important that everyone should start embracing entrepreneurship, go into entrepreneurial action and understand how institutions can help to make this happen. The main objective of this study was to understand the relationship of individual socio-cognitive traits and institutions in increasing an individual’s probability of springing into entrepreneurial action. Majority of the secondary data utilized for this study were sourced from the Global Entrepreneurship Monitor (GEM), Fraser’s Institute, and Transparency International. Multi-level binomial logistic regression random effects modeling was employed using Jamovi software. Findings indicated that socio cognitive traits self-efficacy, alertness to opportunities, social network significantly and positively predicted entrepreneurial action while fear of failure significantly but negatively impacted it . Economic freedom was significant in moderating, albeit negatively, all the above-mentioned cognitive traits in predicting entrepreneurial action as well. And even though the impact of economic freedom is negative, it should not stop national governments in further assisting its citizens towards their dreams of becoming an entrepreneur. Assistance could be in the form of implementing less onerous system of registration with the various agencies of the government in opening up a new business. It was argued that individual who want to be entrepreneurs are willing to comply with government bureaucracy as long as they are given the opportunity to do so. Culture was likewise also established as a negatively significant moderator of alertness to opportunities and social network in predicting entrepreneurial entry. As for the universities providing entrepreneurship courses, results might help encourage the recalibration of curriculums to enhance important socio cognitive traits of entrepreneurship students. Results suggests that social network and alertness to opportunities are significantly influenced by culture upon one’s decision to become an entrepreneur. Universities should then recognize the importance that social network, self-efficacy, alertness to opportunities and fear of failure have on entrepreneurial entry. Curriculums should be designed to provide opportunities for students to strengthen their networking skills, fortify their self-confidence, with the corollary expectations that these will reduce fear of failure while at the same time increase their capabilities in identifying opportunities.